2017
DOI: 10.1002/smr.1855
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of open-source mobile applications: An empirical study

Abstract: Now, mobile applications grow at an exponential speed and their evolution activities are very active, while there is little research on the evolution of mobile apps. To have a better understanding of the evolution of mobile apps and find similarities or patterns in their evolution process, we conduct an empirical study on long spans in the lifetime of 8 typical open‐source mobile apps, which covers 348 official releases. First, we try to verify whether Lehman's laws still apply to mobile apps or not, extract a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 69 publications
0
13
0
7
Order By: Relevance
“…adb shell ./serverscript.sh (1) 2. It should be confirmed that the daemon server is running and has enough permissions to read and manipulate the memory of the device.…”
Section: Methods 6: Dynamic Debugging Of the App In Rooted Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…adb shell ./serverscript.sh (1) 2. It should be confirmed that the daemon server is running and has enough permissions to read and manipulate the memory of the device.…”
Section: Methods 6: Dynamic Debugging Of the App In Rooted Devicesmentioning
confidence: 99%
“…Nowadays, the use of mobile devices is constantly increasing to do the same operations that used to be done using web services less than a decade ago [1,2]. However, it is necessary to provide the same security solutions in both environments since both operations are equally critical.…”
Section: Introductionmentioning
confidence: 99%
“…As a side effect, calls to third‐party libraries are isolated. These have been shown to induce instability to dependent code elements . In order to protect the maturity and functionality of the original implementation, the refactored parts should be protected by tests that can be run after refactoring steps.…”
Section: The Porting Methodsmentioning
confidence: 99%
“…These have been shown to induce instability to dependent code elements. 47 In order to protect the maturity and functionality of the original implementation, the refactored parts should be protected by tests that can be run after refactoring steps. This can be a need for additional tests that cover the adapted code.…”
Section: Extension and Isolation Of The Convertible Cross-platform Corementioning
confidence: 99%
“…Bununla birlikte, yazılım mühendisliği topluluğunda bu yasaları, yazılım evrim problemlerini anlamaya yönelik ve yenilikçi çözümler öneren bir rehber olarak gören bir fikir birliği mevcuttur. Geçen zamanda yazılım mühendisliği disiplini gelişse de yazılımın evrimi üzerine yapılan deneysel çalışmalarla Lehman yasalarının günümüzdeki geçerliliği sınanmakta ve bazılarının hala geçerli olduğu gözlenmektedir [14,15].…”
Section: Gi̇ri̇ş (Introduction)unclassified